Effectiveness of repeated antivenom therapy for snakebite-related systemic complications. Issue 10 (October 2019) - Park, Kyung Hoon; Shin, Hyungoo; Kang, Hyunggoo; Kim, Changsun; Choi, Hyuk Joong; Yoo, Kyunghun; Oh, Jaehoon; Lim, Tae Ho
Objective: This study aimed to determine the effect of repeated antivenom therapy compared with that of single antivenom therapy for treating snakebite-related systemic complications. Methods: A retrospective medical record review from January 2008 to September 2016 was performed. Patients with snakebite injury who visited the Emergency Department in one tertiary center of Korea were included. The primary outcome was the survival rate. The secondary outcome was the effect of repeated antivenom therapy for treating snakebite-related systemic complications compared with that of single antivenom therapy on hospital length of stay. Results: A total of 110 patients with snakebites were included. All patients survived to discharge. Twenty-nine (26.4%) patients had snakebite-related systemic complications. Of these, nine patients received repeated antivenom therapy and 20 patients received single antivenom therapy. The length of stay was significantly longer in those who received repeated antivenom therapy compared with those who received single antivenom therapy (10.0 [4.0–11.0] vs. 3.5 [0–7.0] days). Conclusion: We were unable to demonstrate any superiority of repeated versus single antivenom therapy. However, repeated antivenom therapy is associated with a longer hospital stay. The reason for this finding is unknown.